PEMANFAATAN DIGITAL MARKETING SEBAGAI MEDIA PEMASARAN PRODUK USAHA MIKRO, KECIL, DAN MENENGAH - Rina Fitriana; Sucipto Adisuwiryo; Febriani, Elfira; Najih, Muhammad (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
Hanan's Cake is a Micro, Small, and Medium Enterprise (MSME) in Tangerang, Indonesia. Currently, Hanan's Cake sells and markets via WhatsApp and social media. However, the marketing strategy implemented needed to be more appropriate. Marketing is still relatively traditional, namely by consumers' word of mouth. Digital marketing can be used to help with these problems. This activity aims to increase MSMEs' knowledge regarding digital marketing to help them increase sales of their products and assist them in using one of the digital platforms that can be used for product marketing. Activities are carried out online, identifying problems, helping, and providing examples of the use of social media. Using social media applications for product marketing focuses on uploading photos, providing captions, being creative in taking product photos, and utilizing the features available in social media applications. In the series of activities, participants were very enthusiastic and participated well. Increasing participants' insight into digital marketing can help overcome various business problems and increase MSME income.